1999
DOI: 10.1063/1.371409
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of excimer laser annealing on the structural and electrical properties of polycrystalline silicon thin-film transistors

Abstract: The structural and electrical properties of excimer laser annealed polycrystalline silicon thin-film transistors (polysilicon TFTs) are investigated in relation to the laser energy density. The devices were fabricated on 50 nm thick polysilicon films prepared by excimer laser crystallization (ELA) of amorphous silicon or by a combined solid phase crystallization (SPC) and ELA process. The structural properties of the polysilicon films have been investigated by transmission electron microscopy analysis. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The Beer Lambert's law plays an important role as it relates the absorption of light to the properties of the substrate material (Angelis 1999). The absorption coefficient (µ) depends on medium and wavelength of the incident radiation with intensity (I), which is given as follows:…”
Section: Figure 10 Illustration Of Laser Beam Interaction With a Subsmentioning
confidence: 99%
“…The Beer Lambert's law plays an important role as it relates the absorption of light to the properties of the substrate material (Angelis 1999). The absorption coefficient (µ) depends on medium and wavelength of the incident radiation with intensity (I), which is given as follows:…”
Section: Figure 10 Illustration Of Laser Beam Interaction With a Subsmentioning
confidence: 99%
“…The active polysilicon layers (50 nm thick) were prepared by solid phase crystallization (SPC) of amorphous silicon in a conventional furnace at 600°C for 24 h in nitrogen ambient for grain size enlargement, followed by KrF excimer laser (k = 248 nm) irradiation in air ambient for reduction of the in-grain defect density. Transmission electron microscopy (TEM) analysis has shown that the average grain size is about 2.5 lm, with relatively very high in-grain defect density, in the asgrown polysilicon layer [9,10]. After laser irradiation, although the average grain size remains almost unchanged, the in-grain defect density becomes lower as the laser energy density increases whereas the surface roughness increases due to mass transfer towards the grain boundaries [9].…”
Section: Methodsmentioning
confidence: 99%
“…After laser irradiation, although the average grain size remains almost unchanged, the in-grain defect density becomes lower as the laser energy density increases whereas the surface roughness increases due to mass transfer towards the grain boundaries [9]. In the investigated TFTs, the SPC polysilicon layer was irradiated with laser of energy density 320 mJ/cm 2 , for best device performance due to the optimum combination of the in-grain defect density and surface roughness [9,10]. Following the patterning of the polysilicon layer, a 120 nm thick SiO 2 was deposited by electron cyclotron resonance-plasma enhanced chemical vapor deposition (ECR-PECVD) at 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently special attention has been paid to thin-film transistor (TFT) technology because it is used for large area flat panel displays such as liquid crystal displays (LCD) [11][12]. TFT performance strongly depends on the SiO 2 / Si interface properties [13][14][15]. Conventionally, oxidation [16][17], Plasma Enhanced Chemical Vapor Deposition (PECVD) [18][19][20][21], Low Pressure CVD (LPCVD) [22][23][24] and Atmospheric Pressure CVD (APCVD) [25,26] are used for deposition of SiO 2 on silicon substrate.…”
Section: Introductionmentioning
confidence: 99%